THE TRANSFORMATIVE USE OF USER-GENERATED CONTENT: DISCOVERING THE FINE LINE BETWEEN PERMITTED USE AND COPYRIGHT INFRINGEMENT FROM A MALAYSIAN PERSPECTIVE (UUM Journal of Legal Studies, 2025)
User-generated content or more commonly known as UGC has revolutionized the digital landscape by allowing individuals to create, share, and engage with various forms of copyrighted content across digital platforms. This paradigm shift in content creation and distribution has introduced new challenges in copyright law concerning the transformative use of copyrighted work. Balancing the exclusive rights of the right holder as a content creator and copyright user and the interests of society has become increasingly complex in the face of rapid digital innovation and creative expression. Determining whether the transformative use of copyrighted material qualifies as permitted use under the Copyright Act 1987 within copyright exceptions requires careful consideration of the existing legal framework. Hence, this article aims to explore the ability of the current legal framework to identify the fine line between permitted transformative use and copyright infringement in relation to user-generated content. The results demonstrate that the existing legal scheme does not provide permitted use for transformative use of works without the consent of right holders. This article also seeks to discover the possibility of alternative approaches that could effectively resolve the issues related to the transformative use of user-generated content within the existing legal framework. The outcome of this article is to contribute to a broader discussion surrounding the issues of transformative work and user-generated content.